Bergamot leaf extract treats cardiorenal metabolic syndrome and associated pathophysiological factors in rats fed with a high sugar fat diet. (1st October 2022) - Siqueira, Juliana Silva; Vieira, Taynara Aparecida; Nakandakare-Maia, Erika Tiemi; Palacio, Thiago Luiz Novaga; Sarzi, Felipe; Garcia, Jessica Leite; de Paula, Bruno Henrique; Bazan, Silmeia Garcia Zanati; Baron, Giovanna; Tucci, Luigi; Janda, Elzbieta; Altomare, Alessandra; et al.
Abstract: Bergamot citrus (Citrus bergamia Risso et Poiteau), have been used as a strategy to prevent or treat comorbidities associated with metabolic syndrome parameters, such as cardiorenal metabolic syndrome (CRMS). The aim was to test the effect of bergamot leaf extract on CRMS and associated pathophysiological factors in rats fed with a high sugar-fat diet. Animals were divided into two experimental groups with control diet (Control, n = 30) and high sugar-fat diet (HSF, n = 30) for 20 weeks. Once CRMS was detected, animals were redivided to begin the treatment with Bergamot Leaf Extract (BLE) by gavage (50 mg/kg) for 10 weeks: control diet + placebo (Control, n = 09), control diet + BLE (Control + BLE, n = 09), HSF diet + placebo (HSF, n = 09), HSF + BLE (n = 09). Evaluation included nutritional, metabolic and hormonal analysis; and renal and cardiac parameters. HSF groups presented obesity, dyslipidemia, hypertension, hyperglycemia, hyperinsulinemia, insulin resistance. BLE showed protection against effects on hypertriglyceridemia, insulin resistance, renal damage, and structural and functional alterations of the heart. Conclusion: Bergamot leaf extract shows potential as a therapeutic to treat CRMS in animals fed with a high sugar-fat diet. Highlights: Bergamot leaf extract promoted lower dyslipidemia and Insulin Resistance levels. The extract treated cardiorenal metabolic syndrome, improving organ's function. Bergamot leaf extract stimulates Nrf2 activation.